Role of chlorhexidine in restorative dentistry - Pomacóndor-Hernández, César (2010)
The durability of the union of the restorative materials to the dental tissue is an important requirement to obtain successful treatments in Dentistry. Unfortunately, the hybrid layer formed between the resin and the dentine undergoes degradative processes, of both the resin component such as the collagen. The chlorhexidine is a wide-spectrum antibacterial agent with inhibition capability against the proteolytic activity of some enzymes that can degrade the collagen fibers from the hybrid layer. For that reason, it was recently incorporated to the conventional dental adhesive application protocol. This article reviews studies on scientific literature about the use of chlorhexidine in Restorative Dentistry to increase resindentine unions’ longevity.